Paixões, transgressões e tragédias: as missões populares urbanas e campestres (Província Jesuítica do Paraguai, primeira metade do século XVIII). - Cerveira, Luís Alexandre (Universidade do Vale do Rio do Sinos, 2008)
This dissertation is about the popular Missions - urban and countryside - promoted by Jesuit missionaries in the second half of the eighteenth century, in the broad region under Paraguay´s Jesuítica Company jurisdiction. Reconstitution of the motivations, strategies employed and the effects of these missions on people in urban centres and rural plates areas was made from Ânuas Province Jesuítica of Paraguay Letters, for the period from 1720 to 1760. The analysis I´ve used on this documentation revealed a construction of a speech about passions – the reason of people exceded and lost their self control- urban and countryside plates people lost the moral and respect justifying the promotion of missions for conversion. In the three chapters dissertation, I emphasized the particular, the approximations and the distinctions between urban and countryside popular Missions, as well as focus the passions ,political conflicts and revolutionary actions that occurred in Prata , in the first half of the eighteenth c
Keywords: missões jesuíticas; missões populares campestres; missões populares urbanas; popular missions contryside; jesuit missionaries; popular missions urban; Ciências Humanas